2016
DOI: 10.1016/j.tem.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The Sweet Path to Metabolic Demise: Fructose and Lipid Synthesis

Abstract: Epidemiological studies link fructose consumption with metabolic disease, an association attributable in part to fructose mediated lipogenesis. The mechanisms governing fructose-induced lipogenesis and disease remain debated. Acutely, fructose increases de novo lipogenesis through the efficient and uninhibited action of Ketohexokinase and Aldolase B, which yields substrates for fatty-acid synthesis. Chronic fructose consumption further enhances the capacity for hepatic fructose metabolism via activation of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 102 publications
9
150
0
1
Order By: Relevance
“…Choi et al (82) further showed that the initial oxidative stress in the mitochondria is due to NADPH oxidase, but later there is stimulation of mitochondrial oxidative stress via the electron transport chain, and that these lead to endoplasmic reticulum (ER) stress, the activation of SREBP-1c, and further stimulation of lipogenesis via activation of acetyl CoA carboxylase-1 and FAS (83). Others have also shown fructose-induced induction of the transcription factor, SREBP-1c (83, 108110) as well as the carbohydrate Responsive-Element Binding Protein (ChREBP) (33, 111). The stimulation of ChREBP results in the stimulation of glucose-6-phosphatase that may mediate some of the gluconeogenic effects of fructose (112).…”
Section: Fructokinase the Principal Enzyme Driving Fructose-inducedmentioning
confidence: 99%
“…Choi et al (82) further showed that the initial oxidative stress in the mitochondria is due to NADPH oxidase, but later there is stimulation of mitochondrial oxidative stress via the electron transport chain, and that these lead to endoplasmic reticulum (ER) stress, the activation of SREBP-1c, and further stimulation of lipogenesis via activation of acetyl CoA carboxylase-1 and FAS (83). Others have also shown fructose-induced induction of the transcription factor, SREBP-1c (83, 108110) as well as the carbohydrate Responsive-Element Binding Protein (ChREBP) (33, 111). The stimulation of ChREBP results in the stimulation of glucose-6-phosphatase that may mediate some of the gluconeogenic effects of fructose (112).…”
Section: Fructokinase the Principal Enzyme Driving Fructose-inducedmentioning
confidence: 99%
“…In addition to providing substrate for lipogenesis, chronic fructose consumption increases transcriptional regulation of DNL by activating key transcription factors, including sterol regulatory element-binding protein 1c (SREBP1c) and carbohydrateresponsive element-binding protein (ChREBP) (122). SREBP1c promotes lipid synthesis and is regulated at the transcriptional and posttranslational levels by nutrients and hormones.…”
Section: Genetic Lessons About Fructose Metabolismmentioning
confidence: 99%
“…ChREBP KO mice are intolerant to fructose and have reduced hepatic triglyceride levels and hepatic DNL rates on high-starch diets [13]. Thus, fructose may contribute to hepatic steatosis through at least two mechanisms: 1) by providing substrate for fatty-acid synthesis and esterification in the liver and 2) by stimulating hepatic lipogenic gene programs under the control of ChREBP and other signaling factors [reviewed in [14]]. …”
Section: Introductionmentioning
confidence: 99%